2015
DOI: 10.1103/physreva.91.063411
|View full text |Cite
|
Sign up to set email alerts
|

Probing photoelectron angular distributions in molecules with polarization-controlled two-color above-threshold ionization

Abstract: We present polarization-controlled multiphoton two-color above-threshold ionization (TCATI) of molecules. The intensity modulations of valence photoelectron intensities of molecules arising from varying the relative orientation of the linear polarization vectors of femtosecond infrared (IR) and vacuum-ultraviolet (VUV) radiation in TCATI of the highest occupied molecular orbitals of H 2 O, O 2 , and N 2 are reported. The results on the molecular systems are compared to the 3p photoionization of atomic Ar, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 48 publications
(70 reference statements)
3
14
0
Order By: Relevance
“…The same behavior was reported for laser-assisted photoionization in the case of water molecules, considering of only one harmonic selected from an XUV pulse train in the presence of an IR field [17]. Provided that the energy of the assistant IR laser is substantially smaller than the photoelectron energy, these experiments might be described by means of a simple first-order atomic model developed within the framework of the soft-photon approximation (SPA) [16][17][18]. However, the SPA fails for low and near-threshold photoelectron energies, mainly because of the plane wave (PW) representation of the continuum states.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…The same behavior was reported for laser-assisted photoionization in the case of water molecules, considering of only one harmonic selected from an XUV pulse train in the presence of an IR field [17]. Provided that the energy of the assistant IR laser is substantially smaller than the photoelectron energy, these experiments might be described by means of a simple first-order atomic model developed within the framework of the soft-photon approximation (SPA) [16][17][18]. However, the SPA fails for low and near-threshold photoelectron energies, mainly because of the plane wave (PW) representation of the continuum states.…”
Section: Introductionsupporting
confidence: 69%
“…In order to quantify the degree of polarization control of the total cross-section achieved using the two-photon two-color ionization process, it is convenient to define the sideband intensity modulation as [17]…”
Section: Cross-sectionsmentioning
confidence: 99%
“…are often referred to as partial amplitudes. As seen from expression (23), the angular distribution of the photoelectrons is now determined by a convolution of the sideband amplitudes F with the Fourier coefficients of the vortex Bessel beam a κm (k ⊥ ) from Eq. ( 4) and a phase factor that just contains the impact vector b.…”
Section: Analytical Time Integration Of the Two-color Ati Transition ...mentioning
confidence: 99%
“…Furthermore, it was found that a sideband structure is presented in the photoelectron spectrum as well as the Auger electron spectrum [37][38][39], which can be in favor of the in-vestigation of the properties of pulses reversely. Also, these sidebands have been applied in investigating the molecular orbitals of O 2 , H 2 O and N 2 [40]. Additionally, the ATI spectrum presents a steplike structure when the XUV photon energy is much higher than the atomic ionization potential [41,42] and the dependence of ATI spectrum on polarization direction of two-color laser fields is identified [43].…”
Section: Introductionmentioning
confidence: 99%